Ты и я: Сборник / сост. Л. Антипина - Антипина Л. (библиотека молодой семьи; Т.1, 1988)
Экземпляры: ЧЗ (20151210) / Инвентарный номер: 22691 / Цена: 1.10 / Сис.шифр: 87.71 / Авт.знак: Т 93 / ГРНТИ: 15 / ББК: 87.715.5